Subclinical Ventricular Dysfunction in Long-Term Acromegaly Assessed by Speckle-Tracking Echocardiography - Gadelha, Patricia; Santos, Eduardo C. L.; Castillo, Jose; Vilar, Lucio (Frontiers in Endocrinology, 2022)
Introduction: Symptomatic heart disease may be present in patients with advanced-stage acromegaly. However, earlier assessment of subclinical ventricular systolic dysfunction can be accomplished through speckle-tracking echocardiography (STE) for the study of myocardial strain. The few such studies in this population to date have produced conflicting results. This study was performed to evaluate the parameters of ventricular strain in patients with acromegaly with no cardiac symptoms. Methods: In this prospective observational study, STE was performed in patients with active acromegaly with no detectable heart disease and in a control group to assess ventricular dysfunction through global longitudinal strain (GLS), radial strain, circumferential strain, and twist. The left ventricular (LV) ejection fraction, LV mass index, and relative wall thickness were also compared between the groups. Results: Twenty-five patients with active acromegaly (median age, 49 years; median disease duration, 11 years) and 44 controls were included. LV hypertrophy was more prevalent in the acromegaly group (40% vs. 19%, p < 0.01). The LV ejection fraction was similar between the groups (65.2% ± 5.99% vs. 62.9% ± 7.41%). The mean GLS (−18.8 ± 2.49 vs. −19.7 ± 3.29, p = 0.24), circumferential strain (−16.7 ± 3.18 vs. −16.6 ± 3.42, p = 0.90), and twist (14.6 ± 5.02 vs. 15.1 ± 3.94, p = 0.60) were not significantly different between the groups. Conclusion: Despite showing higher rates of LV hypertrophy, patients with long-term acromegaly had no impairment of ventricular contractility as assessed by strain echocardiography when compared with a control group.